The Domain of the Medium. (Tokyo : The National Museum of Modern Art, 1994)
Akiyama, Yo ; Cha, KeaNam ; Fujiwara, Shiho ; Gen, Shokoku ; Hayashibe, Masako ; Hoshino, Satoru ; Kofushiwaki, Tsukasa ; Sekijima, Hisako ; Suga, Kishio ; Tanaka, Nobuyuki ; Yoon, Hee-Chang
The Domain of the Medium, The National Museum of Modern Art, Tokyo, Oct. 4 - Nov. 27, 1994
English-Japanese
kunstcatalogus